SEG Technical Program Expanded Abstracts 2000 2000
DOI: 10.1190/1.1815598
|View full text |Cite
|
Sign up to set email alerts
|

Where does S‐wave energy on OBC recordings come from?

Abstract: A study of wave-mode conversion that occurs at the sea floor for downgoing seismic energy and a comparison with reflected conversions at a representative interface of Tertiary sediments is presented. To investigate if the presence of S-waves on the vertical component (and Pwave in horizontal) could be due to mode conversion close to the receivers, conversion for up-going seismic energy in the shallow sediments is also analyzed. It is concluded that: 1) most P-to-S conversion occurs as reflection at sediment in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…The processing and modelling of the V x component suggested that P-to-S converted reflections represent the dominant mode, and the detailed processing of this component focused consequently on enhancing P-to-S conversions. These results are consistent with recent synthetic modelling performed by Rodriguez-Suarez et al (2000). The top reservoir reflector can be observed as the first strong dipping reflector at approximately 4500-5000 ms.…”
Section: Interpretation and Modellingsupporting
confidence: 81%
“…The processing and modelling of the V x component suggested that P-to-S converted reflections represent the dominant mode, and the detailed processing of this component focused consequently on enhancing P-to-S conversions. These results are consistent with recent synthetic modelling performed by Rodriguez-Suarez et al (2000). The top reservoir reflector can be observed as the first strong dipping reflector at approximately 4500-5000 ms.…”
Section: Interpretation and Modellingsupporting
confidence: 81%
“…In this paper, geotechnical data are used, through correlation to direct VS measurements, to obtain values for shear-wave velocities in shallow marine sediments. The values obtained in this work were used, together with additional literature data, in analyses of mode-conversion (P-to -S and S-to -P), for both up-and down-going seismic energy at sea-bottom and in shallow marine sediments (Rodriguez-Suarez et al, 2000).…”
Section: Introductionmentioning
confidence: 99%